Pengaruh Digital Marketing, Harga, dan Kualitas Produk Terhadap Keputusan Pembelian pada Konsumen Kopi Kenangan: Pendekatan Regresi Linear Berganda - Adinda Nurul Andira; Dian Saputri; Lulu Permatasari; Ratu Syahlaa’ Qurrotu ‘Ainii; Risma Nurul Fadilah; Sunita Dasman (GLOBAL SCIENTS PUBLISHER, 2026)
This investigation seeks to evaluate how digital marketing, pricing strategy, and product quality contribute to the buying decisions of Kopi Kenangan consumers. A quantitative methodology incorporating a causal linkage approach was implemented. Research data originated from a structured survey disseminated using Google Forms involving 59 respondents between 15–30 years old in Bekasi through the purposive sampling technique. The analytical procedure consisted of validity assessment, reliability evaluation, classical assumption examination, and multiple linear regression analysis supplemented with t assessment, F evaluation, together with coefficient of determination measurement. The study outcomes demonstrate that digital marketing, price, and product quality independently provide a beneficial and statistically validated impact on purchasing decisions. Collectively, these three variables likewise demonstrate a positive and significant contribution, producing an R² of 55.9%, whereas the unexplained variation is associated with variables beyond the proposed model.